2002
DOI: 10.1038/sj.bjp.0704564
|View full text |Cite
|
Sign up to set email alerts
|

The flavonol quercetin activates basolateral K+ channels in rat distal colon epithelium

Abstract: 1 The¯avonol quercetin has been shown to activate a Cl 7 secretion in rat colon. Unlike the secretory activity of the related iso¯avone genistein, quercetin's secretory activity does not depend on cyclic AMP; instead, it depends on Ca 2+ . We investigated the possible involvement of Ca 2+ dependent basolateral K + channels using apically permeabilized rat distal colon epithelium mounted in Ussing chambers. 2 In intact epithelium, quercetin induced an increase in short-circuit current (I sc ), which was diminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Moreover, resveratrol could interact directly with CFTR as this mode of interaction could be shown for other flavonoids, e.g., genistein and quercetin. Indeed, quercetin-induced Cl À secretion was at least in part mediated by activation of basolateral K + channels in the rat distal colonic mucosa (39).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, resveratrol could interact directly with CFTR as this mode of interaction could be shown for other flavonoids, e.g., genistein and quercetin. Indeed, quercetin-induced Cl À secretion was at least in part mediated by activation of basolateral K + channels in the rat distal colonic mucosa (39).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the prosecretory effect of quercetin persisted in the Ca 2+ -free buffer (which was not the case for TDC). It is known that Cl -secretion induced by quercetin does not require the activation of cyclic AMP-activated K + basolateral KCNQ1/KCNE3 channels (Cermak et al, 2002). Although not directly investigated in the present model, this might also apply to the prosecretory effect of TDC.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that quercetin induces Cl -secretion via selective activation of the Ca 2+ -dependent K + basolateral rSK4 channels (Cermak et al, 2002;Devor et al, 1997). Here we show that clotrimazole, an rSK4 channel blocker (Devor et al, 1997), completely inhibited TDC-induced increase in I SC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best known examples are quercetin (a flavonol) and genistein (an isoflavone). Recent studies have shown that quercetin stimulates Cl Ϫ secretion across rat colonic mucosa (11,12). This secretory activity does not depend on cAMP but depends on Ca 2ϩ , possibly via a Ca 2ϩ /calmodulin-dependent pathway.…”
mentioning
confidence: 96%